Цифровое государство и Китай - Вэй, Вэнь (БНТУ, 2021)
Digital country is a new trend of digital economic development and national development. This concept includes many contents, such as digital economy, digital technology, digital services, digital democracy, etc. The comprehensive development of digitalization is an important opportunity for national economic development. Both the Chinese society and the government attach great importance to the construction and development of a digital nation. Many enterprises in China have already succeeded in the field of digitalization based on the Internet. Further development and promotion of digitalization in all fields of society. Summing up successful construction experience is an important issue for China and many countries.